Sisters In Islam’s Quest for The Reinterpretation of The Qur’an and Hadith: An Analysis of Their Views on Equality, Women Judges, and Polygamy - Abdussalam Muhammad Shukri; Musa Yusuf Owoyemi (Kajian Malaysia, 2014)
This article examines the reinterpretation project of an Islamic feminist movement in Malaysia, Sisters In Islam (SIS), by analysing some of its book projects on the issues of equality, women judges in the Shariah Courts, and Islam and polygamy. The article examines the attempts by SIS to reinterpret some Qur'anic verses and the Hadith and to reform Islamic family laws to suit its view of the way that contemporary Muslim society should relate to its women with respect to equality between Muslim men and women, appointing female Muslims as Shariah judges, and eradicating polygamy in Muslim societies. Utilising analytical and critical methods, this research analyses some books written by SIS members on these issues, identifying some plausible points and pointing out misreadings because SIS members did not consider holistic perspectives and situations of contemporary times. Finally, while acknowledging the usefulness of this effort in certain areas, this article rejects the extremism and impracticality in some aspects of works by SIS and calls for a rethinking of the areas in which this movement has erred in its mission to reinterpret verses of the Qur'an and the Hadith and to reform Islamic family law.